Implementation of Human Rights Education Humans in the World of Elementary School Education - Rahma Eka Putri (International Journal of Students Education, 2024)
Implementation human rights education in the world of education Elementary School is one of them important part in education in elementary school. Research purposes this is from desire writer in know how Implementation human rights education in the world of education Elementary school. Method used is qualitative descriptive with approach studies literature. Based on results research, researcher get if Implementation human rights education in the world of education Elementary School is method in introduce children to non- discrimination practices since early and also become method in introduce the concept of human rights since early in children. Research conclusions this is implementation human rights education in the world of education Elementary School becomes business in give human rights education since early.